Prospects for nuclear power plant development in Indonesia: A DPSIR framework analysis for sustainable energy transition, economic implications, and environmental considerations - Triani, Meiri; Azy, Fikri Noor (Jurnal Bisnis Kehutanan dan Lingkungan, 2025)
Background: Coal-fired power plants have historically dominated Indonesia's power sector. Using fossil fuels (coal, oil, and gas) is recognized as the most significant contributor to greenhouse gas (GHG) emissions that cause the climate crisis. Methods: Therefore, this paper examines the possibility of developing a nuclear power plant in Indonesia by conducting a systematic literature review for relevant references and adopting the DPSIR (Driving Force – Pressure – State – Impact – Response) framework. Findings: The result shows that nuclear power applications could be more attractive than the development of other renewable energy sources (wind, solar) in the future because of the non-intermittent low-carbon technology with large output and longer operating life. Besides technical issues, understanding public opinion is essential for creating effective nuclear energy policies. This study emphasizes the crucial factor for Indonesia's future nuclear energy development. The successful implementation of Indonesia's climate action strategy through nuclear power will be enabled by developing collaboration between stakeholders (government, local communities, researchers, and corporate partners) and creating opportunities for international cooperation. Conclusion: The threat posed by global climate change has attracted attention worldwide, including Indonesia. Under Indonesia's ambitious decarbonization target and the issue of energy security, adopting nuclear power in Indonesia's electricity system is considered a significant effort for sustainability in the energy transition in the future. Novelty/Originality of this article: The novelty of this research lies in the systematic approach in analyzing the potential development of nuclear power plants (PLTN) in Indonesia using the DPSIR framework (Driving Force - Pressure - State - Impact - Response).